Математическое моделирование следящего привода - Таванюк, Татьяна Яковлевна (НТУ "ХПИ", 2015)
Представлена типовая нелинейная математическая модель следящего привода с дроссельным регулированием. Математическая модель адаптирована на приводы специального технологического оборудования, построенные на основе стандартных модулей, с использованием для оценки динамических характеристик паспортных данных устройств привода. Даны рекомендации по заданию исходных данных и выбору граничных данных условий для численного моделирования математической системы. Представлена оценка устойчивости, качества регулирования и коррекции динамических свойств привода.

Consider a typical non-linear mathematical model of the servo with the throttle control, taking into account the non-stationary processes. The model has a minimum set of input parameters and is universal for drives, built on the template. However, taking into account the main nonlinearities gives a noticeable gain in calculation accuracy than linear models. This is confirmed by results of numerical modeling of transient processes at different levels of input signals. Recommendations on the initial data shown and the choice of the boundary conditionsdata for the numerical simulation of a mathematical system. It provides an assessment of sustainability, quality control and correction of the dynamic properties of the drive. Mathematical model is adapted to control the special technological equipment based on standard modules are used to estimate the dynamic characteristics of the passport data of the drive.
Mathematical modeling of servo drives
Keywords: электрогидравлический усилитель; математическая модель; динамические характеристики; дроссельное регулирование; servo drive; electrohydraulic power; mathematical model; dynamic characteristics; numerical simulation; transmission coefficients